'Not a Position for a Gentleman': Sir Matthew Nathan as Colonial Administrator: From Cape Coast Castle to Dublin Castle via Natal. Issue 1 (2nd January 2018) - Dominy, Graham
ABSTRACT: This article examines the role of Sir Matthew Nathan, British permanent under secretary for Ireland at the time of the Easter Rising in April 1916, and how critical events in his career as soldier, colonial governor and civil servant shaped his conduct and reaction to events in Ireland as the Rising unfolded around him. The article raises issues of identities: namely Nathan's own identity as an English gentleman, when, given his Jewish background, he was an outsider to that caste. Nathan's brief military career and lengthier career as a colonial governor earned him high praise as a model bureaucrat. In this paper Nathan's track from the War Office through government houses situated in West Africa, Hong Kong and Natal to Dublin Castle is traced to illustrate the changes in his character from decisiveness to indecision. While Nathan clearly misread the volatile situation in Ireland over the 1916 Easter weekend, his actions demonstrated both indecision and bureaucratic delaying tactics. It is argued that his experiences with obdurate settler ministers in Natal played a role in shaping his hesitancy at the time of crisis in Dublin and that this hesitancy provided an opportunity for the direct action of the Irish Volunteers. The conclusion is that, at the time of the Irish crisis, Nathan failed to exercise the 'power of the personal influence' expected of an experienced governor.